China's dominance hypothesis and the emergence of a tri-polar global currency system - Marcel Fratzscher; Arnaud Mehl (European Central Bank (ECB), 2011)
This paper assesses whether the international monetary system is already tripolar and centred around the US dollar, the euro and the Chinese renminbi (RMB). It focuses on what we call China's “dominance hypothesis”, i.e. whether the renminbi is already the dominant currency in Asia, exerting a large influence on exchange rate and monetary policies in the region, a direct reference to the old “German dominance hypothesis” which ascribed to the German mark a dominant role in Europe in the 1980s-1990s. Using a global factor model of exchange rates and a complementary event study, we find evidence that the RMB has become a key driver of currency movements in emerging Asia since the mid-2000s, and even more so since the global financial crisis. These results are consistent with China's dominance hypothesis and with the view that the international monetary system is already tri-polar. However, we also find that China's currency movements are to some extent affected by those in the rest of Asia.
Keywords: F30; F31; F33; N20; 330; China; euro; Exchange Rates; German dominance hypothesis; international monetary system; renminbi; tri-polarity; US dollar; Internationales Währungssystem; Währungswettbewerb; Reservewährung; Wechselkurs; Renminbi; US-Dollar; Euro